please answer these two questions to become brainliest
Attachments:
![](https://hi-static.z-dn.net/files/db0/78abc114d97f103c15f00566073ed00a.jpg)
Answers
Answered by
1
1) (√5+√2)²
=>> 5 +2 + 2√10
=> 7 +2√10
2)(√5+√2)(√5-√2)
=>> 5 -2
=>>> 3
=>> 5 +2 + 2√10
=> 7 +2√10
2)(√5+√2)(√5-√2)
=>> 5 -2
=>>> 3
Answered by
0
1) (√5+√2)²
➡We have an identity:
(a+b)²=a²+b²+2ab
So, (√5+√2)²=(√5)²+(√2)²+2(√5)(√2)
➡5+2+2(√10)
➡7+2√10
2) (√5-√2)(√5+√2)
➡ Another identity:
(a+b)(a-b)=a²-b²
Now,
(√5-√2)(√5+√2)=(√5)²-(√2)²
➡5-2
➡3
Similar questions